Risk factors for residual lesions after total hysterectomy in patients with high-grade cervical intraepithelial neoplasia - Jing Wang; Chao Wang; Tao Su (BMC, 2024)
Abstract Background The purpose of this study was to predict the risk factors for residual lesions in patients with high-grade cervical intraepithelial neoplasia who underwent total hysterectomy. Methods This retrospective study included 212 patients with histologically confirmed high-grade cervical intraepithelial neoplasia (CIN2-3) who underwent hysterectomy within 6 months after loop electrosurgical excision procedure (LEEP). Clinical data (e.g., age, menopausal status, HPV type, and Liquid-based cytology test(LCT) type), as well as pathological data affiliated with endocervical curettage (ECC), colposcopy, LEEP and hysterectomy, were retrieved from medical records. A logistic regression model was applied to estimate the relationship between the variables and risk of residual lesions after hysterectomy. Results Overall, 75 (35.4%) patients had residual lesions after hysterectomy. Univariate analyses revealed that positive margin (p = 0.003), glandular involvement (p = 0.017), positive ECC (p < 0.01), HPV16/18 infection (p = 0.032) and vaginal intraepithelial neoplasia (VaIN) I-III (p = 0.014) were factors related to the presence of residual lesions after hysterectomy. Conversely, postmenopausal status, age ≥ 50 years, ≤ 30 days from LEEP to hysterectomy, and LCT type were not risk factors for residual lesions. A positive margin (p = 0.025) and positive ECC (HSIL) (p < 0.001) were identified as independent risk factors for residual lesions in multivariate analysis. Conclusions Our study revealed that positive incisal margins and ECC (≥ CIN2) were risk factors for residual lesions, while glandular involvement and VaIN were protective factors. In later clinical work, colposcopic pathology revealed that glandular involvement was associated with a reduced risk of residual uterine lesions. 60% of the patients with residual uterine lesions were menopausal patients, and all patients with carcinoma in situ in this study were menopausal patients. Therefore, total hysterectomy may be a better choice for treating CIN in menopausal patients with positive margins and positive ECC.